The Kingdom of Christ The New Evangelical Perspective - Moore, Russell (Wheaton Crossway Books, 2004)
Explores the history and significance of the Kingdom consensus movement. Also analyzes the relationship between Christianity and public policy in the United States.
Keywords: Jesus Christ -- Kingdom. Kingdom of God. Christianity and politics -- United States. Evangelicalism -- United States. Theology, Doctrinal. Jesus Christ. Christianity and politics. Evangelicalism. United States